1977
DOI: 10.1111/j.1365-2125.1977.tb05736.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and metabolism of nomifensine in animals.

Abstract: 1 The absorption, excretion, distribution and metabolism of a new antidepressant agent, nomifensine, was examined in rats, dogs and monkevs. After oral administration ot '4C-nomifensine 1 mg/kg body weight, the compound was absorbed rapidly, and as shown in rats and dogs, virtually completely. Nomifensine was predominantly found in a conjugated form in the plasma of rats, dogs and monkeys. Nomifensine was bound to serum proteins (approximately 60%) and the degree of binding was not species specific. 2 The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Animal experiments have shown that nomifensine is absorbed almost quantitatively (Kellner et al, 1977). Metabolic studies in urine samples indicate a biotransformation to acid-labile and stable conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have shown that nomifensine is absorbed almost quantitatively (Kellner et al, 1977). Metabolic studies in urine samples indicate a biotransformation to acid-labile and stable conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…Reports of metabolite identification in humans in vivo revealed multiple hydroxylated modification at the phenyl ring ( Fig. 1, nomifensine hydroxylated metabolites I, II, and III), suggesting that a reactive ortho-quinone (through the oxidation of catechol at the C ring) or a quinone-methide (through the oxidation of phenol at the C ring) intermediate could be formed (Kellner et al, 1977;Heptner et al, 1978;Hornke et al, 1980;Lindberg and Syvälahti, 1986;Kalgutkar and Soglia, 2005). However, no GSH adducts of nomifensine arene oxidative intermediates have been reported.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Generation and sequestration of such a metabolite within tissues, such as blood cells or hepatocytes, could be a possible cause of toxicity. However, in the early reports describing the metabolism of nomifensine in vivo, no observation of a dihydroisoquinolinium ion was made (Kellner et al, 1977;Heptner et al, 1978;Hornke et al, 1980;Lindberg and Syvalahti, 1986). No reports on the metabolism of this compound using in vitro methods have been described.…”
mentioning
confidence: 99%
“…In an examination of the metabolism of nomifensine in vivo, the observed metabolites included alterations of the phenyl ring, including conjugates suggesting the existence of a catechol intermediate metabolite (Kellner et al, 1977;Heptner et al, 1978;Hornke et al, 1980;Lindberg and Syvalahti, 1986). These represent two possibilities of structural elements in nomifensine that could underlie the toxicity of the drug.…”
mentioning
confidence: 99%